Parental and staff perspectives of NICU research procedures - Freibott, Christina (BMC Pediatr, 2016)
BACKGROUND: There are limited data on parental perception of infant participation in minimal risk and minor increase above minimal risk research focusing on the NICU population. The study objective was to assess parental and NICU staff perceptions concerning minimal risk and minor increase above minimal risk in the NICU setting. METHODS: Parents of infants and NICU staff were presented with a combination of 4 infant scenarios and 5 hypothetical research procedures. These assessed participants’ willingness to allow their infant to participate in research and their attitude towards obligation to assist future children. Linear and hierarchal linear models analyzed the association and interaction effects on the likelihood to consent to research procedures. RESULTS: Sixty parents and 30 NICU staff members were surveyed. Parents’ acceptability for each of the five research procedures ranged from 31 % to 83 %. Parent gender, age, race/ethnicity, insurance, education and history of previous child in the NICU were not associated with the likelihood to consent to the research procedures. Acceptability for each of the five research procedures among NICU staff ranged from 19 % to 98 %. There were no significant differences between NICU staff’s and parents’ responses for 4 of 5 research procedures. A minority of parents and nurses (38.3 % and 40 % respectively), compared to a majority of physicians (66.7 %), agreed or strongly agreed that parents have a responsibility to involve their children in low risk medical research in order to help future children, even if this would not help their own child. Lower agreement with obligation to help future children (p < 0.01) and higher education (p = 0.01) were associated with a decreased likelihood to consent to research procedures. CONCLUSION: In our study population, common NICU-related research procedures were considered appropriate and acceptable to a diverse group of NICU parents representing a wide range of race/ethnic and socioeconomic strata. Current regulations guiding informed consent for minimal and minor increase over minimal risk research in the NICU environment appear ethically consistent with a diverse group of parents and providers.